Life-threatening complications in childbirth: a discursive analysis of fathers' accounts. (27th May 2019) - Moore, Hannah; Solomons, Wendy; Hinton, Lisa
ABSTRACT: Objectives : To explore the discursive construction and social actions achieved by accounts given by men following a birth in which the mother developed life-threatening complications. Background : Existing qualitative research employing interpretative thematic analysis of men's accounts of births in which the mother developed life-threatening complications highlights men's expressions of distress and marginalisation. This paper extends this, adopting different epistemological and analytic approaches to those accounts. Methods : Audio recordings and transcripts of semi-structured interviews collected by Hinton et al. were re-analysed using an approach informed by narrative analysis, discursive psychology and the discursive action model. Participants were four white British men whose partners experienced a maternal 'near-miss' event. Results : This analysis illustrates how men in this study draw on cultural narratives of 'normal' birth to construct experiences. Narrative constructions highlight separation of health professionals from laymen. These men use a discourse of self-reliance within families to construct their path to recovery. Conclusion : The strength of available narratives of birth and limited accessibility of alternative ones may impact how men tell their experience. Men in this study discursively attend to issues of power, agency and male identity, re-establishing entitlement to speak about their experience, but construct emotional support as unavailable to them.